2006
DOI: 10.1038/sj.cr.7310028
|View full text |Cite
|
Sign up to set email alerts
|

How the Bcl-2 family of proteins interact to regulate apoptosis

Abstract: Commitment of cells to apoptosis is governed largely by protein-protein interactions between members of the Bcl-2 protein family. Its three sub-families have distinct roles: the BH3-only proteins trigger apoptosis by binding via their BH3 domain to pro-survival relatives, while the pro-apoptotic Bax and Bak have an essential downstream role involving disruption of organellar membranes and induction of caspase activation. The BH3-only proteins act as damage sensors, held inert until their activation by stress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
236
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(246 citation statements)
references
References 115 publications
(155 reference statements)
10
236
0
Order By: Relevance
“…While the ratio of Bcl2 to Bax is considered a rheostat of cell life or death, the Bcl2 family includes multiple pro-survival proteins, including Bcl2 and Bcl-xL, either of which can associate with Bax either directly or via BH3-only proteins (Korsmeyer et al 1993;Finucane et al 1999;Cheng et al 2001;van Delft and Huang 2006). Similarly, both Bax and related pro-cell death family members such as Bak can induce mitochondrial membrane permeabilization and subsequent activation of downstream cell death pathways van Delft and Huang 2006). It is therefore possible that a Bax association with an unidentified pro-survival protein is necessary for neomycin ototoxicity, while Bcl2 interacts with Bak or another prodeath protein in gentamicin-induced damage pathways.…”
Section: Bcl2 Proteins and Aminoglycoside Ototoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the ratio of Bcl2 to Bax is considered a rheostat of cell life or death, the Bcl2 family includes multiple pro-survival proteins, including Bcl2 and Bcl-xL, either of which can associate with Bax either directly or via BH3-only proteins (Korsmeyer et al 1993;Finucane et al 1999;Cheng et al 2001;van Delft and Huang 2006). Similarly, both Bax and related pro-cell death family members such as Bak can induce mitochondrial membrane permeabilization and subsequent activation of downstream cell death pathways van Delft and Huang 2006). It is therefore possible that a Bax association with an unidentified pro-survival protein is necessary for neomycin ototoxicity, while Bcl2 interacts with Bak or another prodeath protein in gentamicin-induced damage pathways.…”
Section: Bcl2 Proteins and Aminoglycoside Ototoxicitymentioning
confidence: 99%
“…Bax is a member of the Bcl2 family that acts by forming channels in the mitochondrial outer membrane, facilitating cytoplasmic translocation of mitochondrial proteins such as cytochrome c and activation of downstream cell death signaling (Putcha et al 1999;Wei et al 2001;Scorrano and Korsemeyer 2003). Through this route, Bax is closely associated with caspase activation and classical apoptosis (reviewed in van Delft and Huang 2006;Tait and Green 2010). However, Bax is also necessary for mitochondrial changes and activation of downstream cell death pathways in a caspase-independent manner (Middleton et al 2000;Besirli et al 2003;Cheung et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This showed that individual BH3-only proteins are activated only in response to certain apoptotic stimuli and not to others. The physiological roles of the different BH3-only proteins have been reviewed elsewhere (Strasser, 2005;van Delft and Huang, 2006).…”
Section: The Bh3-only Proteinsmentioning
confidence: 99%
“…In apoptotic conditions, Bax translocates from the cytosol to the mitochondria, oligomerizes, and inserts into the OMM in concentrated foci [34]. This process results in the formation of a pore through which apoptotic factors stored in the intermembrane compartment are released [34].…”
Section: Signaling Pathways Of Apoptotic Cell Deathmentioning
confidence: 99%
“…This process results in the formation of a pore through which apoptotic factors stored in the intermembrane compartment are released [34]. Similarly, Bak, which is constitutively anchored to the OMM, can form homo-oligomeric complexes upon apoptotic stimulation [34]. Bax/Bak hetero-oligomers have also been described [35].…”
Section: Signaling Pathways Of Apoptotic Cell Deathmentioning
confidence: 99%